Computed tomographic heterogeneous enhancement of spleen in healthy cats: comparing with diffuse infiltrative splenic lesions - Lee, Yooyoung; Chang, Dongwoo; Kim, Sojin; Oh, Miju; Ban, Jiyoung; Lee, Minju; Chang, Jinhwa; Ahn, Jisoo; An, Taegeon (Frontiers in Veterinary Science, 2024)
Contrast-enhanced computed tomography (CT) of the spleen in dogs and cats often displays a heterogeneous enhancement pattern. This study aimed to describe the CT appearances and duration of heterogeneous splenic enhancement in clinically healthy cats and to compare those enhancements with diffuse infiltrative splenic lesions (DISL). Spleens of 14 healthy cats were imaged using contrast-enhanced CT protocols which were obtained at 10, 25, 45 seconds and then every 40 seconds thereafter until 245 seconds from the initiation of contrast medium injection. The presence of transient splenic heterogeneity was evaluated. In addition, the relationships of certain variables including age, weight, systolic blood pressure, and splenic volume to the duration and the degree of splenic enhancement were determined. Also, medical records and CT images of 5 cats with DISL were retrospectively evaluated. Transient heterogeneous enhancement of the spleen was observed in all 14 healthy cats, and the maximum heterogeneity was observed 25 seconds after the injection. Splenic heterogeneity lasted more than 5 minutes in nine of 14 cats (64.3%). No statistically significant relationships were seen between the duration and degree of splenic heterogeneity in the images taken 25 seconds after the injection and variables including weight, age, systolic blood pressure, and splenic volume. Compared to the healthy group, early homogeneous splenic enhancement along with generalized splenomegaly was observed in all cats with DISL. Transient splenic heterogeneity is highly common in cats undergoing contrast-enhanced CT even in the generally scanned delayed phases which can help with the interpretation of CT images of feline spleens. In addition, our results suggest that homogeneous splenic enhancement in post-contrast CT scans along with splenomegaly on CT images could be useful as a diagnostic indicator of DISL in cats.